Decrease of FZD4 exon 1 methylation in probands from FZD4-associated FEVR family of phenotypic heterogeneity - Liu, Miaomiao; Luo, Jia; Feng, Huazhang; Li, Jing; Zhang, Xiang; Zhao, Peiquan; Fei, Ping (Frontiers in Medicine, 2022)
Familial exudative vitreoretinopathy (FEVR) is an important cause of childhood blindness and is clinically characterized by phenotypic heterogeneity. FEVR patients harboring the same genetic mutation vary widely in disease severity. The purpose of this study was to explore nongenetic factors that regulate FEVR phenotypic heterogeneity. We detected methylation levels of 21 CpG sites located at the FZD4 exon 1 region of 11 probands, 12 asymptomatic/paucisymptomatic carriers and 11 non-carriers from 10 unrelated FZD4-associated FEVR families using bisulfite amplicon sequencing (BSAS) . Our results showed reduced methylation level of FZD4 exon 1 in probands, suggesting that FZD4 exon 1 methylation level may be negatively linked with FEVR disease severity. It provided a new research direction for follow-up research, helping us better understand the complexity of the FEVR-causing mechanism.